Perspektif Iman Remaja akan Keselamatan tentang Pacaran dan Pernikahan Beda Agama - Budiatmaja, Rudy; Djojosuroto, Kinayati (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Many teenagers say that love can be blind and that love can be carried out by men and women of different religions because of the wrong understanding which states that it is just a momentary pleasure and only satisfies a man's lust without following the current rules or norms of decency. The aim of the current research is to prioritize Soteriology as a spiritual provision for teenagers to face changes in their attitudes and face the wider social circle of all teenagers who are entering the transition period from childhood to adulthood, which includes all growth and development in relationships because of this the church and family are present. to teach the truth about the realities of life. Qualitative literature study methods are used to obtain accurate data related to this scientific work, the sources are the Bible, books and other articles related to the title discussed. The research results show the doctrine of soteriology and the role of the church as a teaching